"SAKTI SEHAT” SERIES AS AN INNOVATIVE VISUAL, INFORMATIVE, AND EVIDENCE-BASED HEALTH EDUCATION MEDIA : FIRST SERIES: GRAVES’ DISEASE - Rahman, Ave Olivia (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2025)
Graves’ disease, a form of hyperthyroidism, is less familiar to the public compared to other metabolic disorders such as diabetes mellitus. This literature review was conducted to gather scientific information about the disease, with a particular focus on its pharmacological management. Public knowledge about Graves’ disease can be enhanced through literacy and health education initiatives. Therefore, a booklet will be developed based on this review as a medium to support community literacy activities and improve awareness and understanding of Graves’ disease. The “SAKTI SEHAT” series will be developed for other health themes relevant to addressing Indonesia’s health problems.